Learning difficulties among foreign pupils in primary school - Μυλωνά Άννα; Κούτρας Βασίλειος (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2018)
Migration, economy globalization, international communication networks creation, new technologies, easy access to knowledge, cultural values redefinition and the new universal cultural models creation have led to new data and issues in relation to the education in Europe and globally, as well as in Greece which from a sending country is being transformed in migrants receiving country. Modern intercultural pedagogical current expressing cultural plurality and difference is addressed not only to cultural and linguistic minorities of the school community but to all the students. Increasing migrants’ mobility with the resulting educational problems has led to international organizations reaction as well to important initiatives in Greece and Europe in general, indicating the will to change the attitude towards minority education and intercultural education promotion.